2014
DOI: 10.1021/ac4036789
|View full text |Cite
|
Sign up to set email alerts
|

Logic Control of Enzyme-Like Gold Nanoparticles for Selective Detection of Lead and Mercury Ions

Abstract: Functional logic gates based on lead ions (Pb(2+)) and mercury ions (Hg(2+)) that induce peroxidase-like activities in gold nanoparticles (Au NPs) in the presence of platinum (Pt(4+)) and bismuth ions (Bi(3+)) are presented. The "AND" logic gate is constructed using Pt(4+)/Pb(2+) as the input and the peroxidase-like activity of the Au NPs as the output; this logic gate is denoted as "Pt(4+)/Pb(2+)(AND)-Au NPPOX". When Pt(4+) and Pb(2+) coexist, strong metallophilic interactions (between Pt and Pb atoms/ions) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…Recently, many works have discovered that mercury ions could interact with other metal nanoparticles to form bimetallic NPs4748. In addition, it was also confirmed that the citrate around the surface of metal NPs was essential to promote the process of these combinations.…”
mentioning
confidence: 92%
“…Recently, many works have discovered that mercury ions could interact with other metal nanoparticles to form bimetallic NPs4748. In addition, it was also confirmed that the citrate around the surface of metal NPs was essential to promote the process of these combinations.…”
mentioning
confidence: 92%
“…3 Recently, many metallic nanoparticles with enzyme-like activity, termed as "enzyme mimics", have attracted considerable interest. 17 These enzyme mimics have demonstrated broad application in detecting various targets, such as metal ions, 18,19 anions, [20][21][22] small molecules [23][24][25] and nucleotide acid, 26 etc. Among various metallic nanoparticles, the (gold core)@ (platinum shell) nanoparticle possessed unique catalytic properties and attracted special attention.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, much effort has been devoted to the construction of novel artificial enzymes as highly stable and low-cost alternatives to natural enzymes. A series of inorganic nanomaterials including Au NPs [3], Fe 3 O 4 NPs [4], Co 3 O 4 NPs [5], V 2 O 5 nanowires [6], carbon dots [7], graphene oxide [8], single-walled carbon nanotubes [9] and metallic nanocomposites [10] have been found to present unexpected enzyme-like activities. As the most known one, noble metal platinum (Pt) is chemically inert at bulk scales but can serve as the important catalysts at nanoscales because of their unique size, shape and the increased specific surface area [11].…”
Section: Introductionmentioning
confidence: 99%